Detection of single-mode thermal microwave photons using an underdamped Josephson junction - A. L. Pankratov; A. V. Gordeeva; A. V. Chiginev; L. S. Revin; A. V. Blagodatkin; N. Crescini; L. S. Kuzmin (Nature Communications)
Abstract When measuring electromagnetic radiation of frequency f, the most sensitive detector counts single quanta of energy h f. Single photon detectors have been demonstrated from γ-rays to infrared wavelengths, with ongoing efforts to extend their range to microwaves. Here we show that an underdamped Josephson junction can detect 14 GHz thermal photons, with energy 10 yJ or 50 μeV, stochastically emitted by a microwave copper cavity at millikelvin temperatures. After characterizing the source and the detector, we vary the cavity temperature and measure the photon rate. The device achieves 45% efficiency and a dark count rate of 0.1 Hz over several GHz. Demonstrated super-Poissonian photon statistics is a signature of thermal light and a hallmark of quantum chaos. We discuss applications in dark matter axion searches and note its relevance to quantum information and fundamental physics.